Visible-near infrared spectroscopy and near-infrared hyperspectral imaging for the detection of T-2 and HT-2 toxins in individual oat grains - Teixido-Orries, Irene; Molino, Francisco; Agusti-Fernandez, Pau; Ayibiowu, Ebenezer; Croucher, Derek; Medina, Angel; Marín, Sonia; Verheecke-Vaessen, Carol (Elsevier, 2026)
Oat grains are increasingly consumed worldwide due to their health benefits, yet they are highly susceptible to contamination by Fusarium toxins, particularly T-2 and HT-2 toxins (T-2+HT-2). These toxins pose serious health risks and are unevenly distributed, with a few highly contaminated grains often driving a batch over legal safety limits. Current detection methods are destructive, slow, or inadequate for detecting contamination at the individual grain level. This study is the first to demonstrate the potential of visible–near-infrared (Vis-NIR) spectroscopy and near-infrared hyperspectral imaging (NIR-HSI) to detect T-2+HT-2 in individual oat grains non-destructively. 200 grains were scanned, and their toxin content quantified by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Classification models were developed to identify grains exceeding both the European Union (EU) legal threshold (1250 μg/kg) and a higher risk level (10,000 μg/kg). Both techniques achieved high accuracy (up to 94.5 %) in identifying contaminated grains. Key wavelengths were identified (e.g., 1203, 1419, 1424 and 1476 nm in NIR; 440–455 nm in Vis), and reducing the model to 20 wavelengths preserved performance while simplifying computation. Critically, removing just 21.5 % of the most contaminated grains could reduce overall toxin levels by over 95 %. Moreover, sampling simulations revealed that analysing 30 % of grains guarantees detection of contamination above legal limits, whereas 0.5 % sampling yields only a 25–33 % detection chance. These findings highlight a feasible path for integrating spectroscopic screening into industrial oat sorting lines, improving food safety, reducing economic losses, and overcoming key limitations of conventional mycotoxin monitoring.
Keywords: Applied mycology; T-2 toxin; HT-2 toxin; Near-infrared; Vis range; Spectroscopy; Oat; Cereal sorting; 30 Agricultural, Veterinary and Food Sciences; 40 Engineering; Food Science; 3006 Food sciences; 4004 Chemical engineering